Dampak Program Bantuan Operasional Sekolah (BOS)Terhadap Tingkat Putus Sekolah Di Indonesia: Analisis DID - Kharisma, Bayu (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 1, Februari 2013 (pp. 1-70), 2013)
This study aims to analyze the impact of school operational assistance (BOS) program on the dropout rate of school during the post-rising fuel prices using difference in difference (DID) approach. BOS program is a further development of the social safety net programs (JPS) education of the government in the period of 1998-2003 and a reduction in fuel subsidy compensation program implemented over 2003-2005. The results showed that the impact of BOS on the dropout rate of students aged 7-15 years, during the period investigated in this study was lower than those who did not receive BOS fund, but it was not statistically significant. Meanwhile, if the account of the research is to be limited to the influence of students aged 16-20 years who had previously received the benefit of  BOS, it shows that BOS program had a positive influence to the dropout rates of school. However, children aged 16-20 years who had not previously received benefits BOS program have negatively affect to the dropout rates of school. Based on this fact, the benefit of the BOS proram following the fuel price hike in Indonesia during the research  period did not seem to be particularly effective in reducing the dropout rates of school.
Keywords: school operational assistance (BOS) program; dropout rate of school; rise of fuel price in Indonesia; difference-in-difference